An evaluation of the revenue side as a source of fiscal consolidation in high debt economies. Issue 6 (4th November 2014) - Banerjee, Ritwik
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Unsustainable levels of debt in some European economies are causing enormous strain in the Euro area. Successful debt consolidation in high-debt economies is the single most important objective for the European policy makers. The paper aims to discuss these issues. Design/methodology/approach – The author uses a dynamic general equilibrium closed economy model to compute the dynamic Laffer curves for Portugal, Ireland, Greece and Spain for different class of taxes. The general equilibrium effects of the interaction of labor tax, consumption tax and capital tax is demonstrated. Findings – Location of each economy on its Laffer curve suggests that there exists a scope for considerable revenue generation by raising consumption and labor tax rates but no such possibilities exist for capital tax rate. Thus revenue generation with certain tax rates as instruments, holds key to successful and sustained debt reduction. Originality/value – This to the best of knowledge is one of the first papers which looks closely at the tax revenue – tax rate panel for the major deeply indebted European economies.